Anti-inflammatory activity of 5-(3,4-dihydroxyphenyl)-3-hydroxy-1-(2-hydroxyphenyl)penta-2,4-dien-1-one (synthetic curcuminoid analogue) in mice - Hisamuddin, Nadia (2019)
The rhizome of Curcuma longa (C. longa) plant consists of 3-5% curcuminoids. Curcuminoids comprises of curcumin, demethoxycurcumin and bisdemethoxycurcumin. Among these, curcumin has been reported to be responsible for most of the C. longa pharmacological activities. However, the biological activities of curcumin are limited due to its solubility and low bioavailability in vivo. Numerous curcuminoid analogues with better bioavailability and solubility were synthesized to overcome these limitations. Novel synthetic curcuminoid analogues such as the 5-(3,4- dihydroxyphenyl)-3-hydroxy-1-(2-hydroxyphenyl)penta-2,4-dien-1-one (abbrev. DHHPD), showed good anti-inflammatory activities in vitro. Hence, the current study was conducted to evaluate the anti-inflammatory activity of DHHPD in mice using the carrageenan-induced paw oedema and cotton pellet-induced granuloma tests. Mice that received DHHPD (0.1, 0.3, 1 and 3 mg/kg, intraperitoneal) showed a significant decrease (p<0.05) in paw oedema formation from the 2nd hour of induction until the end of the experiment. The inhibition induced by DHHPD at 0.1, 0.3, 1 and 3 mg/kg (intraperitoneal) were 65.4%, 66.9%, 73.8% and 86.9% respectively. In the cotton-pellet induced granuloma test, DHHPD (0.1, 0.3, 1 and 3 mg/kg, intraperitoneal) showed significantly marked reductions (p<0.001) in granuloma development by 22.1%, 32.6%, 37.2% and 49.3%, respectively. The possible mechanisms of action involved in DHHPD-induced anti-inflammatory effect were evaluated using histamine-, serotonin-, and bradykinin-induced paw oedema tests. Results showed that DHHPD (0.1, 0.3, 1 and 3 mg/kg, intraperitoneal) caused significant (p<0.05) reductions in paw oedema formation induced by the intraplantar administration of histamine (100 μg/paw) from the 10th minute until the 40th minute after induction. DHHPD demonstrated significant reductions in the formation of serotonin-induced (100 μg/paw) paw oedema in the 1st hour and from the 3rd to 5th hour whereas bradykinin-induced (10 nmol/paw) paw oedema was significantly reduced by DHHPD throughout the experiment (1st to 5th hour). In conclusion, DHHPD exerted anti-inflammatory effects in the rodent models of induced inflammation possibly through the histaminergic, serotonergic and bradykininergic systems.